Perceptions of Agricultural Commodity Traders on the Effectiveness of the Traditional Market Revitalization Program in Bengkulu City - Fachrul Irhami Dhita; Gita Mulyasari; Irnad Irnad (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2023)
Revitalization is an alternative path that must be taken by traditional markets in order to compete in the globalization era. The role of traditional markets will continue to be degraded and reduced if adequate facilities are not immediately repaired. This is due to the increasing number of modern markets emerging so that with the revitalization, it is expected that traditional markets can compete with modern markets. This study aims to analyze the effectiveness of the traditional market revitalization program in Bengkulu City and its relationship to revenue, number of consumers, working hours, and user fees. This research was conducted intentionally with the purposive sampling method. Respondents in the study amounted to 55 people spread over three traditional markets in Bengkulu City, namely Panorama Market, Minggu Market, and Barukoto Market. The results of the study show that the overall revitalization program for traditional markets in Bengkulu City is quite effective. Based on correlation analysis, variable acceptance, number of consumers, and working hours have a positive correlation to the effectiveness of the traditional market revitalization program in Bengkulu City. Meanwhile, another variable, namely user fees, has no correlation with the effectiveness of the traditional market revitalization program in Bengkulu City.